Pengenalan dan Pelatihan Mengenai Cloud Kitchen–Small Business Culinary: Dessert Kepada Siswa-Siswi SMA/SMK - Juliana Juliana; Amelda Pramezwary; Wulan Meiaya Wowor; Sandra Maleachi; Demson R H Goeltom (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Community service is an activity carried out to increase a sense of care for the surrounding community by sharing knowledge and skills. The objectives of community service activities are (1) To share knowledge and skills possessed by students through courses at the Faculty of Tourism, Pelita Harapan University, (2) To introduce high school / vocational high school students about Cloud Kitchen - Small Culinary Business with the theme dessert (3) To apply the knowledge and knowledge obtained by students through studies at the Faculty of Tourism, Pelita Harapan University. Therefore, the Community Service team created a community service activity program in the form of workshops by teaching high school / vocational high school students about Cloud Kitchen and its benefits amid the Covid-19 pandemic and teaching participants how to make dessert at home. It is hoped that this activity can be useful for SMA / SMK students and can be developed.